Destroying Humanity Physically And Virtually Via Human Trafficking - Singh, Vikas Pratap (Trinity Law Review, 2021)
The world is made up of elements but the language we all understand is only humanity, which means that humans are born with equal rights and equal dignity. No one shall be deprived of his rights assured by nation as well as the nature. In 1948 when United Nation declared Universal Declaration of Human Rights (UDHR). In general, human rights are the protection of natural rights as well as fundamental rights of every individuals. No one has right to compel any human to be the labor with or without wages, to be a slave without dignity, to be sex worker without self-respect etc. Human Trafficking is practiced generally to fulfil the requirement of labor, slave, wives, as well as children, within a country as well as at international levels. We have strict laws at National and international level. If we consider the Article 23, of Constitution of India, which talks about human labor and trafficking in human, Section 370 & 370A etc. Of Indian Penal Code, 1860(IPC). When we deny Fundamental Rights Of individuals, then indirectly we deny the human rights assured by Indian laws as well as United Nations Human Rights Commission (UNHRC). For instance, people from Nepal, Bhutan, Pakistan, India etc. are abducted or kidnapped and are send to far off places like Thailand, Russia, Ukraine, Sri Lanka etc. Human trafficking is the most preferred form of exploitation of humans at National and international levels. Making laws, enacting them timely, doing survey is beneficial but, something which is missing is the trust on the government by citizens they are easily influenced by person of other states or countries for the promise of money, job and facilities with which they want to live their life. Government of the countries are unable to control their citizens from being exploited by engaging them in a well-equipped employment. The main reason behind this kind of activity is poverty, lack of education, lack of technology and the most important one is lack of belief in government and laws.